2014
DOI: 10.1016/j.ccr.2014.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndromes Are Propagated by Rare and Distinct Human Cancer Stem Cells In Vivo

Abstract: In the version of this article originally published online on May 15, 2014, there was an error in the presentation of the data in Figure 1G. The colors used to represent myeloid and erythroid colony-forming cells (CFCs) for del(5q) patients were inversed, such that myeloid CFCs were shown in black and erythoid CFCs in gray. In both the print and online versions of the article, this error has now been corrected, with the myeloid CFCs being shown in gray and the erythroid CFCs in black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(98 citation statements)
references
References 0 publications
5
92
0
1
Order By: Relevance
“…1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts. With this approach, we were able to identify IL8 as one of the few genes most significantly overexpressed across different stem and progenitor subsets in AML and MDS patients, indicating it might play a crucial role in the pathogenesis of AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts. With this approach, we were able to identify IL8 as one of the few genes most significantly overexpressed across different stem and progenitor subsets in AML and MDS patients, indicating it might play a crucial role in the pathogenesis of AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite the use of poly-chemotherapy and the development of newer agents, clinical outcome remains poor. The disease course is frequently characterized by relapse or failure to achieve durable remission, indicating that current treatment regimens do not target the cancer-initiating cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similar scenarios where mutations were acquired in the mature compartments have also been reported in a recent study by Woll et al 1 One of the limitations of our sequencing analysis is that any mutation present at <2% mutant allele burden (MAB) will not have been detected. Thus, we could not exclude the possibility that ASXL1 and ANGPTL5 gene mutations were acquired in the HSC fraction, but remained at low level (below our detection level) until the cells reached the MPP stage and expanded.…”
Section: A B C Dmentioning
confidence: 85%
“…[1][2][3] Despite their genetic heterogeneity, they share common phenotypic features including low peripheral blood counts (cytopenias) in spite of a hypercellular bone marrow (ineffective hematopoiesis), dysplasia and a variable propensity for transformation to acute myeloid leukemia (AML). 4 Programmed cell death or apoptosis of white blood cells is a common feature, and is thought to contribute to the cytopenias particularly in early stages of the disease.…”
mentioning
confidence: 99%